Tangled Tales of Mycelium and Architecture: Learning From Failure - McGaw, Janet; Andrianopoulos, Alex; Liuti, Alessandro (Frontiers in Built Environment, 2022)
Architects, artists and engineers around the world have been experimenting with the potential of mycelium, the vegetative body of a fungus, as a future building material for the past 15 years. It shares many of the positive material attributes of polystyrene but unlike the synthetic material it is fully sustainable and completely biodegradable. Mycelium has also proved to be simple to grow at scale. Its capacity to rapidly grow its tangled hyphae in a multiplicity of directions, digesting nothing more than organic waste, has shown promise for the production of a variety of materials for the building industry. But despite this, mycelium has struggled to find a market within the building industry. Drawing on the literature, this article argues that the challenges have been psychological, aesthetic and economic, rather than technical. Western industrial systems have conditioned us to expect material cultures to be clean, precise and durable. Mycelium is messy and some fungi are known pathogens. Like any living creature it can be unpredictable. Further, while the materials for growing mycelium are cheap, initial production costs for mass production and distribution typical of industrial fabrication are high. The risk for investors in the absence of an assured market stymied early forays into production. But as the environmental crisis becomes more urgent, there is evidence of a growing interest in finding new avenues for production. Centralised large-scale production is only one way forward. Another, which learns from early failures, is mass production through a multiplicity of micro-scale, do-it-yourself systems.